Delicate Co-operation - Developing County - Illés, Balázs (Theory, Methodology, Practice – Review of Business and Management, 2012)
When I chose the topic of my dissertation I wanted to get involved in a research that can be useful for my home region and can use the resources of my country in the most efficient way. On first sight Hungary is obviously an agricultural country with great tillable areas so the initial “ingredients” are given. Nevertheless my mission held some surprises. First I had to focus on a special area of agribusiness sector which is quite difficult considering the numerous relations of this sector to others as bio-fuels, food processing, tourism, etc. The basic step was to examine the sector as an integral entity. These studies showed the fundamental problems of the field but did not lead to further steps. Regardless of this fact I tried to collect good practices throughout the European agricultural and food clusters. Some essential assumptions can be derived from these data for the visions and field of activity but most of them cannot tell about the formation of these clusters. Of course they had tradition in the specific area but Hungary has also (at least from our point of view) a successful history in agriculture and husbandry. This paper is an introduction to the agricultural cluster possibilities in Hungary examining the specialties in the agricultural sector, and it tries to give an idea of a combined way of creating small agribusiness clusters and bringing business opportunities into the region.